Increasing trends of malaria in a border area of the Greater Mekong Subregion - Jinting Geng; Pallavi Malla; Jiaqi Zhang; Shiling Xu; Cuiying Li; Yan Zhao; Qinghui Wang; Myat Phone Kyaw; Yaming Cao; Zhaoqing Yang; Liwang Cui (Malaria Journal, 2019)
Abstract Background Intensive malaria transmission along international borders is a significant impediment to malaria elimination in the Greater Mekong Subregion (GMS) of Southeast Asia. Passive case detection (PCD) was used to study the dynamics and trends of malaria transmission at the China–Myanmar border to provide epidemiologic information for improved malaria control. Methods PCD was conducted in one hospital and 12 clinics near the Laiza town in northeast Myanmar from 2011 to 2016. Clinical malaria was diagnosed by microscopy and demographic information was captured using a structured questionnaire at the time of the patient’s presentation for care. Results Over the study period, 6175 (19.7%) malaria cases were confirmed by microscopy from 31,326 suspected cases. The four human malaria parasite species were all identified, with Plasmodium vivax and Plasmodium falciparum accounting for 5607 (90.8%) and 481 (7.8%) of the confirmed cases, respectively. In contrast to the steady decline of malaria in the general GMS, the study site had an upward trend of malaria incidence with vivax malaria outbreaks in 2013 and 2016. Adult males, children under the age of 15, and those with occupations such as farming, being a soldier or student, had significantly higher risks of clinical malaria compared to having fevers from other aetiologies. A self-reported history of clinical malaria was also associated with a higher risk of confirmed malaria. Conclusions The China–Myanmar border area has experienced an overall upward trend of malaria incidence in recent years with P. vivax becoming the predominant species. Evidence-based control strategies need to focus on high-risk populations.